Wstręt a erotyzm. Houellebecqa spojrzenie na miłość - Rychlik, Agata (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
„Erotism plunges human into loneliness” – this is an argument put by Georges Bataille in his book Erotism. Isolation resulting from deceptive carnality accompanies heroes of Michel Houellebecq novels as well. This state leads them to feeling of emptiness and emotional burnout. One of the reasons of this state lies in learned carnality. In Bataille’s conception those modeled behaviour can be refered to things that are not allowed, tabooised and relegated to intimate space. Problems that tire Houellebecq’s heroes end with compulsive behaviours performed by them. Those acts exceed social rules, deepen feeling of alienation and rejection. Men of Houellebecq world can’t name their needs and there for they replace them with needs that are created by consumer society. Fulfillment of those superficial desires unfortunetly doesn’t resolve the problem of isolation, it lingers them into desire that brings with itself repulsion and feelings of guilt.
Keywords: erotyzm; wstręt; Houellebecq; tabu; seks